Effect of temperature cycling on performance of epoxy resin and evaluation of state. (September 2019) - Chen, Xiwen; Lu, Bing; Zhang, Dandan; Zhang, Jun; Chen, Jingting
Abstract: Epoxy resin samples were prepared according to the most common types of epoxy resins and curing agents in the market. The material was temperature-circulated at -40 to 150°C to investigate the effect of temperature cycling on the dielectric properties and bending properties of the material. The results show that with the increase of the number of temperature cycles, the relative dielectric constant, dielectric loss, flexural strength and flexural modulus of epoxy resin increase first, then decrease and then increase, and the electrical conductivity increases. Based on the samples of various performance values of epoxy resin in different times, an evaluation model based on BP neural network was established to evaluate the state of epoxy resin.